2018
DOI: 10.4103/ccd.ccd_810_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diode laser-assisted flap surgery on postoperative healing and clinical parameters: A randomized controlled clinical trial

Abstract: Background and Objectives:Lasers have been widely used because of several potential benefits such as antibacterial effect and stimulation of wound healing. In addition, lasers help in hemostasis and delaying epithelial migration which may facilitate the outcome of flap surgery. Hence, this study is aimed to investigate the adjunctive effect of diode laser irradiation on conventional access flap surgery in the treatment of periodontal disease.Materials and Methods:A total of 23 patients requiring periodontal fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Our study showed an insignificant reduction in gingival inflammation for both the groups from baseline. Similar results were reported by Jonnalagadda et al [ 28 ] The decrease in GI can be attributed to the effective removal of calculus and diseased granulation tissue leading to reduction in gingival inflammation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study showed an insignificant reduction in gingival inflammation for both the groups from baseline. Similar results were reported by Jonnalagadda et al [ 28 ] The decrease in GI can be attributed to the effective removal of calculus and diseased granulation tissue leading to reduction in gingival inflammation.…”
Section: Discussionsupporting
confidence: 88%
“…However, there are insufficient evidences to support the adjunctive use of diode laser in periodontal flap surgery. [ 28 29 30 31 32 ] Hence, this study was designed to evaluate the same.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported no additional advantages for DL with conventional access flap debridement than periodontal flap alone. 19 Moreover, Lobo and Pol 20 reported more gingival inflammation reduction in DL associated with flap surgery than flap surgery alone; however, their study did not show any difference in PPD and CAL in the intergroup comparison.…”
Section: Discussionmentioning
confidence: 89%
“…During the first stage, 104 studies were excluded based on the evaluation of titles and abstracts (inter-reviewer agreement, kappa statistic = 0.92). Second, after screening the full-text articles of the remaining 23 studies, 13 studies were excluded because of inappropriate study design [15][16][17][18][19][20] and irrelevant outcome measurement [21][22][23][24][25][26][27] (S1 Table) and 10 eligible studies [28][29][30][31][32][33][34][35][36][37] (five for HLLT, four for PBMT, and one for both HLLT and PBMT) were included in this systematic review (interreviewer agreement, kappa statistic = 0.91). Of these, four studies [29,31,33,34], which showed adequate continuous data concerning the pain level measured with VAS score, were included in the meta-analysis.…”
Section: Search and Selection Resultsmentioning
confidence: 99%